2020
DOI: 10.1016/j.bmc.2020.115820
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine alkaloids with activity in the central nervous system

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 180 publications
(572 reference statements)
1
31
0
Order By: Relevance
“…9,10 In plants, they are mostly found in the alkaloids. 11 In biological systems, redox reactions of nicotinamide adenine dinucleotide (NAD) reduces its pyridine ring into dihydropyridine, rendering NADH. Similar redox reactions are also present in anabolic reactions involving NAD phosphate (NADP + /NADPH) interconversion.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In plants, they are mostly found in the alkaloids. 11 In biological systems, redox reactions of nicotinamide adenine dinucleotide (NAD) reduces its pyridine ring into dihydropyridine, rendering NADH. Similar redox reactions are also present in anabolic reactions involving NAD phosphate (NADP + /NADPH) interconversion.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds comprise mixtures of volatile, complex hydroalcoholic oil-soluble compounds, which are used as cosmetics and pharmaceuticals. Their structures are as follows: Acyclic and monocyclic monoterpenes (1,8-cineole, alfa pinene, camphor, linalool, nerol, and geraniol), bicyclic and tricyclic monoterpenes (sabinene, thujone, and tricyclene), sesquiterpenes (e-nerolidol, carvacrol methyl ether, germacrene B, and cadalene), isoprenoides, and terpenoids that include aldehydes, ethers, alcohols (carvacrol, thymol, eugenol, and borneol), and sulfur- or nitrogen-containing compounds (diallyl disulfide and indole) [ 84 , 85 ]. Mentions of essential oil plants, essential oils, and their derived single constituents appear in pharmacopoeias and traditional medicine paradigms of different cultures.…”
Section: Plants Used In Traditional (Folk) Medicine In Latviamentioning
confidence: 99%
“…The cooled reaction mixture was stirred for 30 min, then reaction was brought to room temperature and stirred for further one hour. The reaction mixture was 8,127.6,122.4,118.4, 7,133.8,127.4,121.4,118.4, 4,129.2,127.4,123.5,121.4,119.2,118.4, 5,158.2,148.0,141.3,137.0,136.7,133.8,130.4,127.4,123.6,121.4,118.4,116.3…”
Section: Synthesis Of Boc Tryptophan (2)mentioning
confidence: 99%
“…During the last two decades, numerous kinds of alkaloids were isolated from the natural sources and studied their importance in biological and pharmaceutical applications [3,4]. Clinically natural alkaloids are famous to treat central nervous system (CNS) disorders for instance atropine, physostigmine morphine, anatabine and papaverine etc [5]. Studies have revealed that wide range of natural alkaloids are biologically active molecules and have been using to treat many pathogenic diseases [6].…”
Section: Introductionmentioning
confidence: 99%